Saúde mental de profissionais da Psicologia que atuam junto a mulheres em situação de violência doméstica: uma revisão integrativa - Santos, Darlene Ferreira dos (Universidade Federal do Tocantins, 2023)
The objective of this study is to analyze the scientific production on the mental health of psychologists who work in the service network for violence against women, asking whether work as violence impacts the mental health of these professionals. The research methodology is defined as an integrative literature review and was delimited to analyze scientific articles published on the subject in Brazil between 2006 and 2022 in the Scielo, BVS and Lilacs databases, using combinations of descriptors Mental health, Violence against women , Psychologist, Psychology and Occupational Health. From the analysis and results, it is observed that violence affects and harms the mental health of professionals, reflecting on the care offered to users. In addition, there is helplessness and precariousness on the part of the State in relation to mental health and working conditions. Finally, it is concluded that it is necessary to broaden the discussion on the mental health of these professionals, in order to enable better health conditions in the work environment.